Design of experiment to maximize tensile strength an impact resistance of wood tile boars from recycled plastics and bagasse - Atienza, Rumel V. (Animo Repository, 2008)
Plastic and bagasse are environmental pollutants that are potential materials for wood tile boards because of their chemical and mechanical properties. Tiles of various combinations of weight percentage of plastic, bagasse, and flame retardant were experimented on to determine the optimal combination with respect to impact resistance and tensile strength. The experiment was designed to minimize number of samples, avoid sampling bias and maintain a high level of confidence. The optimal combination even proved to be superior to two commercially available wood tiles.